Pharmaceutical Software Quality Assurance System Architecture - Koteska, Bojana; Pejov, LJupcho; Mishev, Anastas (CEUR-WS.org, 2016)
The risk-based nature of the pharmaceutical computer software puts it in a critical software category which imposes a must quality assurance and careful testing. This paper presents the architecture and data model of a quality assurance system for computer software solutions in pharmaceutical industry. Its main goal is to provide an online cloud solution with increased storage capacity and full time authorized access for quality checking of the developed software functionalities. The system corresponds to the requirements of the existing standards and protocols for pharmaceutical software quality. This system aims to ease the process of pharmaceutical software quality assurance process and automate the document generation required for quality document evidence.